O novo ensino médio e as práticas curriculares do trio gestor no Centro de Ensino Educa Mais Sousândrade - SANTOS, Flávya Soraya Mendes Machado dos (2024)
This research addressed the New High School and the Curricular Practices of the managing trio. The research site investigated was the Centro de Ensino Educa Mais Sousândrade high school, which is located in Bairro do Lira. The general objective of the research was to: analyze the impact of the New Secondary Education in Maranhão on the functions of the managing trio of schools in Tempo Integral Educa Mais, with a view to producing a guidebook with the specific administrative pedagogical functions of each managing subject. The research questions were: What are the documents and practices adopted in our State in Full-Time High Schools? What conceptions, knowledge and pedagogical knowledge do state network managers need to have in view of the perspectives of the New High School? How do managers develop and record their curricular practices? How could a pedagogical notebook of narratives contribute to the praxis of other managers of the State Network? The Dissertation is divided into five sections, namely: the Introduction; Introducing School Management; Conceptualizing Narratives and their impacts on the work of school managers; The New High School and the Narratives of the Trio Gestor at Centro Educa Mais Sousândrade; Returning to the methodological path: Narratives on the scene in the lines and between the lines of research. The educational product is a Pedagogical Guidance Notebook where, after eight meetings, managers will build a portfolio with narratives relevant to issues in the socio-emotional sphere that permeate the managers' curricular practice and involve their subjectivities and, to date, few records. We proposed activities based on music, peer listening, academic texts and a lot of reflection on the curricular practices of the managing trio. We are anchored in Normative Instruction No. 04/2020/PPGEEB/UFMA, which made the applicability of the educational product optional. The bibliographic sources that supported the research were: Libâneo (2001), Silva (2010), Lombardi (2010), Silveira (2018), Vasconcelos (2007), Zambelo (2019), among others. With regard to methodological options, Minayo (1996), Fazenda (2015) and Richardson (1999). With an emphasis on the curricular and narrative part, we also point out Oderich (2009), Paraíso (2023), Souza (2011). The data collection instruments used were observation, interviews via Google Forms to survey the profile of each manager, and a survey using an Excel spreadsheet of the duties most used in each manager's practice. The data was systematized, analyzed and interpreted based on the categories of research interest and gathered into response tables that will make up a mosaic of curricular practices that the new high school provides to the management trio. The narratives are an element of partnership that points to the often silenced voices of the managing trio.